Feasibility of Papaya Seeds and Rice Flour as Traditional Scrubs for Dry Skin - Alga Ningsih; Murni Astuti (Universitas Negeri Padang, 2022)
This research was backgrounded by a bath of papaya seeds with the addition of rice flour as one of the basic ingredients of traditional cosmetics as a scrub for dry skin. This study aims to a) To analyze the feasibility of rice flour and papaya seeds as traditional scrubs for nurses, the feasibility of rice flour and papaya seeds will be achieved as traditional scrubs for body care based on organoleptic tests, b) To analyze how the feasibility of rice flour and papaya seeds as traditional scrubs for body care based on organeleptic tests, c) To analyze the feasibility of rice flour and papaya seeds as traditional scrubs for body care based on favorability tests. This research uses a quantitative approach to the type of pre-experiment method. The place and time of the study was conducted at the FMIPA Laboratory and the Cosmetology and Beauty Laboratory of FPP UNP in January 2022. The object of study is papaya seeds and rice flour. The data source used was a panelist of 7 people, namely 1 beauty doctor, 1 chemical analyst, 2 lecturers and 3 Cosmetology and Beauty students who had passed the cosmethodology and facial skin care courses. The variables in this study are free variables (x) and bound variables (y). Data collection techniques use observation and documentation with descriptive analysis techniques that display frequency and percentage. Based on the results of the study obtained in seeds per 100 gr of Vitamin B1 by 0.0004% and Tannins by 0.0031%. Judging from the results of organoleptic tests, it showed that 43% of the panelists stated a rough texture, 57% of the panelists stated that the aroma of papaya seed scrub and rice flour was strongly scented, and 71% of the panelists stated that the stickiness of papaya seed scrub was sticky and based on the panelists' preferences showed that 85% of the panelists stated that they liked papaya seed scrub and rice flour. It is suggested that you can apply the results of this study as a science to increase knowledge about traditional scrubs for skin care.